Keluarga Berencana in Islamic View through a Sociological Approach - Tazkia Anugraheni Perdana (Spiritus: Religious Studies and Education Journal, 2023)
The program that has long been promoted to reduce the population growth rate in Indonesia is "Keluarga Berencana". This research aims to find a middle ground between Islam and the Keluarga Berencana program through a sociological approach. This research method is qualitative. The results and discussion of this research include the verses of the Qur'an and hadith that talk about offspring in Islam, as well as the opinions of scholars about the use of contraceptives. This study concludes that the Keluarga Berencana program should not only be about talking about the number of children but also the quality of the family. And there are justified reasons for the use of contraceptives so that it does not always become haram.